Impact resistance of reinforced concrete members - Low, Kun Sheng (2015)
As building structures became modernized, there is an increased need to understand the behaviour of concrete structures against extreme loading conditions such as impact, blast and earthquakes. In this paper, we will focus on the impact resistance of reinforced concrete members. Generally, concrete displays low resistance towards impact loading due to its low ductility and poor energy absorption. Upon impact, concrete will typically display a variety of cracking failures. In this paper, we shall compare the impact resistance of 5 types of concrete beam. These 5 types of concrete beam are: 1) Normal concrete; 2) Normal concrete with steel fibre reinforcement; 3) Lightweight concrete; 4) Lightweight concrete with steel fibre reinforcement; 5) Normal concrete with steel fibre reinforcement and engineered cementitious composite protective layer. Lightweight concrete was chosen as two of the test specimens due to their properties of lower density and higher strength-to-weight ratio. This decreases the dead load of the building, thereby reducing the strength requirements for structural design and foundation. Steel fibre reinforcement was added to three of the test specimens as literature review has shown that fibre-reinforced concrete has enhanced strain or deflection hardening capacities under excessive tensile or flexural loading. Lastly, one of the test specimens has an added engineered cementitious composite (ECC) protective layer. This protective layer was added to demonstrate its ability to act as a sacrificial layer to protect the concrete. Within the scope of the study, it was determined that the impact resistance of the specimen with ECC protective layer is the greatest, with its protective layer significantly absorbing the impact energy which results in its debonding from the concrete beam. Steel fibres were also found to improve the impact resistance of concrete beams. However, lightweight concrete was observed to have better energy dissipation mechanisms which reduce their flexural deformation. Following the experimental program, the potential of using LS-DYNA software to model impact loading was explored. After creating a model of the drop weight experiment using LS-PrePost, the experiment was successfully simulated with the concrete beam model displaying realistic physical behaviour. Future work could include further validation of the LS-DYNA model so that we can reduce the need to conduct more physical experiments, thereby reducing time and resources.